Complex and Emotionally Risky - A Study of the Dynamic Challenges in the Artistic Profession and Leadership in Arts Organisations - Wennes, Grete (Senate Hall Academic Publishing, 2012)
By studying two Norwegian arts organisations: The Norwegian National Opera & Ballet and the Oslo Philharmonic Orchestra; this article takes a closer look at the performers – the artists. The article addresses two issues: what are the main challenges facing an artist in an arts organisation and what are the leadership needs these challenges create. The objective is to bring light on the artistic profession at a micro level to fill a void in the literature on arts management. The study identifies three dynamic challenges that seem to be crucial in an artistic profession and are therefore central to understanding leadership in this context. A profession in the arts seems to be complex and emotional risky, constantly shifting between competition and cooperation, nervousness and flow, even for employed artists in an arts organisation. From a leadership perspective this seems to create a need for leadership that is both demanding and supportive.
Keywords: artistic profession; arts management; challenges; competition; cooperation; leadership